The role of microfinance on women's entrepreneurship development in Western Ethiopia evidence from a structural equation modeling: Non-financial service is the way forward - Abraham Abebe; Meketaw Kegne (Cogent Business & Management, 2023)
Microfinance institution services are emerging as a potent tool for poverty eradication and aim to decrease poverty and empower women. However, fewer women than men manage and run businesses in many parts of the world. Therefore, this study investigates the role of microfinance services on women's entrepreneurship development in Benishangul Gumuz Credit and Saving Institution Assosa town, Western Ethiopia. The study employed an explanatory research design and a quantitative approach. The data for the study were collected from 165 respondents using a five-point structured questionnaire and analyzed through the statistical package for social science (SPSS) 26 and AMOS 23 software. A Confirmatory Factor Analysis is employed to establish the construct validity and reliability of the measurements. Then, the Structural Equation Model was used to test the hypotheses developed to examine the effect of microfinance institutions on women's entrepreneurship development. The findings from the structural equation analysis indicated a positive and significant effect of access to finance and saving on the development of women's entrepreneurship. Finally, the structural equation model analysis finding revealed that the microfinance institution's service significantly positively affected women's entrepreneurship development.
Keywords: 650; access to finance; business support; microfinance; saving; skill training; structural equation model; women entrepreneurship